Finite element analysis of Soret and Dufour effects on unsteady MHD free convection flow past an impulsively started vertical porous plate with viscous dissipation - Reddy, M Gnaneswara; Reddy, N Bhaskar (Journal of Naval Architecture and Marine Engineering, 2011)
The free convection flow of an unsteady magnetohydrodynamic and viscous dissipating fluid past an impulsively started vertical plate with soret and dufour effects has been analyzed. With appropriate transformations the boundary layer equations are transformed into nonlinear ordinary differential equations. The local unsteady similarity solutions of the transformed dimensionless equations for the flow. These equations are solved numerically by a finite element method. Favorable comparisons with previously published work are obtained. The effects of the various parameters on the velocity, temperature and concentration profiles as well as the skin-friction coefficient, Nusselt number and Sherwood number are presented graphically and in tabulated form. DOI: http://dx.doi.org/10.3329/jname.v8i1.3507